(untitled) - Armentrout, David; 1962-; Armentrout, Patricia; 1960- (Vero Beach, FL, 2001)
A simple introduction to the life and work of Florence Nightingale, the nineteenth-century English woman considered to be the founder of modern nursing.
Includes bibliographical references and index.
Keywords: Nightingale, Florence; 1820-1910; Juvenile literature; Nurses; Biography; England